The mediating role of management information systems in the relationship between knowledge management and its impact on technology transfer: Applied Study on the managers and officials of information systems management at Education Ministry in Kuwait - Ashkanani, Mariam Ghloum (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to examine the mediating role of management information systems in the relationship between knowledge management and its impact on technology transfer: Applied Study on the managers and officials of information systems management at Education Ministry in Kuwait. Three hypotheses were examined: knowledge management has a positive relationship with management information systems, knowledge management has Positive relationship with technology transfer. Management information systems mediate the relationship between knowledge management and technology transfer. Data and information were collected by surveying a sample of 200 employees using a comprehensive enumeration method. The results showed that there is a positive contribution of knowledge management to improving the role of management information systems, and that there is a positive correlation between knowledge management and technology transfer, in addition to having a positive mediating role for management information systems that contribute to enhancing the positive role of knowledge management towards technology transfer.